A Note on Incentives in Large Economies - Champsaur, Paul; Laroque, Guy (Review of Economic Studies, 1982)
Nash equilibria of anonymous and efficient mechanisms are studied in economies with a continuum of traders. Conditions are given under which some or all the Nash equilibria of such mechanisms yield competitive allocations. Particular attention is payed to the case of direct mechanisms where the truth constitutes a Nash equilibrium.